A bio-based elastomer from cornstalk pith scaffold and natural rubber complexing with ferric ions: Preparation and mechanical properties. (23rd March 2022) - Meng, Yi; Zhang, Chenwei; Gong, Xiaoyu; Lu, Jie; Cheng, Yi; Tao, Yehan; Wang, Haisong
Abstract: Commercial cushioning foam and adhesive tape are commonly produced from petrochemicals, leading to disadvantages like lack of/slow degradation and unsustainability. Herein we designed a polymer composite made from cornstalk pith (a cellulose-based porous scaffold) and a natural rubber as substitution for commercial cushioning foam. Cornstalk pith was firstly pre-treated with FeCl3 to remove lignin and form micro-porous structure and then, interpenetrated with a natural rubber to generate a strengthened construct. The metal ions acted as junctions for combining the two components and resulting the generation of dynamically reversible bonds. When loading was added to the material, these bonds would break and dissipate the added loading, and then after the loading was removed, they would spontaneously reconstruct. The elasticity of the cornstalk was enhanced by the filling and entanglement of the rubber, while the revisable bonds giving by ferric ions and the rubber with good elasticity works synergistically to form a bio-based elastomer with good mechanical properties. The anti-fatigue performance of all samples was investigated through a 100 times cyclic compression tests, displaying a 95% height recovery, which is better than commercial cushioning foam samples. The good cushioning performance, sustainability, ease preparation process, environmentally friendliness, low cost of the prepared bio-based elastomer shows great potential for industrialization and replacing current petrochemical-based products. Graphical abstract: Image 1 Highlights: Natural occurring porous polysaccharide, cornstalk pith (CSP) is used as scaffold. CSP is filled and enhanced by nature rubber (NR) to form a durable elastomer. Dynamically reversible bond between CSP and NR is constructed by junction ions. Dynamically reversible bond endows the elastomer good anti-fatigue performance. The entire biobased elastomer can be fully used to substitute for commercial products.